Exploring green grain production pathways: evidence from farmland and agricultural service scale operations in China - Han, Guoying; Liu, Tongshan (Frontiers in Sustainable Food Systems, 2025)
To address the pressing issues caused by the excessive use of agricultural chemicals—such as farmland degradation, heightened ecological risks, and health hazards—and to promote green agricultural production, this study focuses on two key pathways of modern agricultural development: service-based scale operations supported by Agricultural Productive Services (APS), and farmland scale operations. It systematically investigates their respective impacts on the reduction of agrochemical inputs. Using panel data from China’s Rural Fixed Observation Points and employing a system of simultaneous equations with a control function approach to address potential endogeneity, the study empirically examines how APS and farmland scale operations influence agrochemical input use. The results show that: (1) APS significantly reduce the intensity of chemical fertilizer and pesticide (CFP) application in grain production. Specifically, a 1% increase in APS usage is associated with an average decrease of 0.93 CNY per mu in fertilizer costs and 0.07 CNY per mu in pesticide costs. (2) Moderate-scale farmland operations significantly and positively contribute to reducing agrochemical use. (3) Crop-specific analysis reveals that both APS and moderate-scale operations reduce pesticide use in wheat, rice, and maize production. Regarding fertilizer use, APS is more effective for wheat, while farmland scale expansion proves more effective for maize. Both approaches contribute to fertilizer reduction in rice cultivation. These findings provide robust empirical evidence supporting the promotion of APS and appropriately scaled farmland operations as effective strategies to reduce agrochemical inputs and advance sustainable agricultural development.